PTOV1 promotes cisplatin-induced chemotherapy resistance by activating the nuclear factor kappa B pathway in ovarian cancer - Shen, Hongwei; Liao, Bing; Wan, Zhiyong; Zhao, Yunhe; You, Zeshan; Liu, Jun; Lan, Jin; He, Shanyang (Molecular therapy. Oncolytics, 2021)
Chemotherapy resistance is a bottleneck for ovarian cancer treatment; therefore, revealing its regulatory mechanism is critical. In the present study, we found that prostate tumor overexpressed-1 (PTOV1) was upregulated significantly in ovarian cancer cells and tissues. Patients with high PTOV1 levels had a poor outcome. In addition, PTOV1 overexpression increased CDDP (cisplatin) resistance, while PTOV1 knockdown inhibited CDDP resistance, as determined using cell viability assays, apoptosis assays, and an animal model. Mechanistic analysis showed that PTOV1 increased nuclear factor kappa B (NF-κB) pathway activity, reflected by increased nuclear translocation of its p65 subunit and the phosphorylation of inhibitor of nuclear factor kappa-B kinase subunits alpha and beta, which are markers of NF-κB pathway activation. Inhibition of the NF-κB pathway in PTOV1-overexpressing ovarian cancer cells increased CDDP-induced apoptosis, suggesting that PTOV1 promoted chemotherapy resistance by activating the NF-κB pathway. In summary, we identified PTOV1 as a prognostic factor for patients with ovarian cancer. PTOV1 might be a target for inhibition of chemotherapy resistance. [Display omitted] Chemotherapy resistance is a bottleneck of ovarian cancer treatment. In this study, we found PTOV1 not only served as a prognostic factor for ovarian cancer patients but also was a novel target for inhibition of cisplatin resistance.